1977
DOI: 10.1002/star.19770290304
|View full text |Cite
|
Sign up to set email alerts
|

The Rǒle of Starch in Baked Goods Part 2. The Influence of Purification Procedure on the Surface Properties of the Granule

Abstract: Starch was extracted from wheat by a wet‐grinding process and purified by differential centrifugation followed by shaking with toluene and water. The contrast in pasting, surface and baking properties between dried impure, and dried purified, samples of the starches shows that the surface properties of the granules are profoundly affected by the presence of indigenous “non‐starch material”. These effects can be eliminated by utilizing the non‐dried starch, or by removing such non‐starch material by shaking wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…"Surface" proteins between 5 and 30 kDa on "A-grade" cereal starch granules can be removed by agitation at RT with either aqueous salt solutions such as 0.1 M NaCl [9,17], 0.05 M NaCl containing 50% (v/v) propan-2-ol [57], a 1 or 2% solution of SDS (optionally with 1% β-2-mercaptoethanol (2-ME) [5,12,13,29,41,55,58], or 10 mM dithiothreitol (DTT) [5]), SDS-PAGE sample buffer solutions [59], 50% (v/v) propan-2-ol [57] or with toluene [8]. It is now known, however, that these extraction methods are unlikely to fully extract "surface" SGAP; Schofield and Greenwell [12] reported that dilute NaCl extracts only 10% of the total SGAP (substantially more than 10% of SGAP is "surface" protein -see Section 3.4 below); Rahman et al [30] have demonstrated that 1 or 2% solutions of SDS do not give maximum yields of SGAPs, and that 10% SDS solutions are probably preferable (although this remains to be verified with "surface" proteins).…”
Section: Extraction Of Starch Granule-associated Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…"Surface" proteins between 5 and 30 kDa on "A-grade" cereal starch granules can be removed by agitation at RT with either aqueous salt solutions such as 0.1 M NaCl [9,17], 0.05 M NaCl containing 50% (v/v) propan-2-ol [57], a 1 or 2% solution of SDS (optionally with 1% β-2-mercaptoethanol (2-ME) [5,12,13,29,41,55,58], or 10 mM dithiothreitol (DTT) [5]), SDS-PAGE sample buffer solutions [59], 50% (v/v) propan-2-ol [57] or with toluene [8]. It is now known, however, that these extraction methods are unlikely to fully extract "surface" SGAP; Schofield and Greenwell [12] reported that dilute NaCl extracts only 10% of the total SGAP (substantially more than 10% of SGAP is "surface" protein -see Section 3.4 below); Rahman et al [30] have demonstrated that 1 or 2% solutions of SDS do not give maximum yields of SGAPs, and that 10% SDS solutions are probably preferable (although this remains to be verified with "surface" proteins).…”
Section: Extraction Of Starch Granule-associated Proteinsmentioning
confidence: 99%
“…Direct evidence of the technological importance of the starch granule "minor" components at the granule surface arises from investigation of the role of starch-protein interactions during baking and the improving action of various treatments such as chlorination, acetylation and heat treatment on the baking quality of flour [8,10,114,[119][120][121][122]. The effects of chlorination on both flour and isolated starch granules have now been extensively studied.…”
Section: The Technological Importance Sgaps and Their Role In Starch mentioning
confidence: 99%
See 1 more Smart Citation
“…An attempt was therefore made to remove a significant proportion of the wedge protein by ultracentrifugation. This technique was chosen so as not to disturb the natural granular surface components since Cauvain, Gough & Whitehouse (1977) have shown that even simple washing processes can cause significant changes in the properties of the starch. The results for the starch fractions in model batter systems I11 and IV (Table 5 ) show a highly significant effect due to the flour proteins.…”
Section: Rheological Testing Of Hot Batter Systemsmentioning
confidence: 99%
“…Exterior surfaces of the starch granules can play an important role in defining their chemical properties and modifications [20][21][22][23][24]. A branch of SFM where the SFM probe is chemically modified to have specific functional group is known as scanning chemical force microscopy (CFM).…”
Section: Introductionmentioning
confidence: 99%